2013
DOI: 10.1080/07399332.2012.755980
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Knowledge, Attitudes, and Practices (KAP) of the Women Referred to Health Centers for Cardiovascular Disease (CVDs) and Their Risk Factors

Abstract: Hypertension, dyslipidemia, and diabetes are established risk factors for cardiovascular disease (CVD) morbidity and mortality. In the past decade a general increase in CVD risk factors in the population aged 65 and older, along with suboptimal control rates, have occurred. In this descriptive, cross-sectional study, the authors describe the knowledge, attitudes, and practices (KAP) of Iranian females regarding risk factors for CVD, in an attempt to help with the development of strategies to control risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 20 publications
5
14
3
Order By: Relevance
“…Smoking was identified as the most common risk factor in this study, which is consistent to that reported in Pakistan [ 16 ], but higher than that stated in previous studies from North Ireland, Canada, Iran, the Gulf countries, Jordan, South Africa, and Nepal [ 14 , 15 , 17 , 19 22 ]. The current results indicate a better knowledge about unhealthy diet as a risk factor when compared to previous reports from Pakistan, North Ireland, Jordan, and South Africa [ 12 , 14 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Smoking was identified as the most common risk factor in this study, which is consistent to that reported in Pakistan [ 16 ], but higher than that stated in previous studies from North Ireland, Canada, Iran, the Gulf countries, Jordan, South Africa, and Nepal [ 14 , 15 , 17 , 19 22 ]. The current results indicate a better knowledge about unhealthy diet as a risk factor when compared to previous reports from Pakistan, North Ireland, Jordan, and South Africa [ 12 , 14 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…Chest pain was the most common known symptom (50.4%), which is close to that found in Beijing [ 23 ], but higher than that in Pakistan [ 12 ] and Nepal [ 22 ]. In contrast, a higher knowledge was reported by previous studies from North Ireland, Canada, Iran and Jordan, where chest pain was known by over 75% of respondents [ 14 , 15 , 17 , 20 ]. Shortness of breath was recognized by 48.0% of the study population, which is consistent to that reported in North Ireland, Canada and Jordan [ 14 , 15 , 20 ], but higher than that in Pakistan and Nepal [ 12 , 22 ].…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In another study, secondhand exposure to smoke causes heart diseases, which increases the risk of disease by approximately 25-30% (Pope III et al, 2011). Moreover, the participants showed lower knowledge related to physical inactivity as risk factors when compared with study conducted in Iran (Mazloomy et al, 2014). Eating fresh fruits and vegetables keeps your heart healthy.…”
Section: Discussionmentioning
confidence: 91%